2022
DOI: 10.1007/s10342-022-01508-x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of intraspecific variation in seed size: does the presence of small seeds reduce predation on large ones?

Abstract: Seeds produced by individual plants often vary substantially in size. Typically, larger seeds produce seedlings that have higher chances of establishment and survival relative to seedlings produced by smaller seeds. However, larger seeds are also preferred by granivores due to larger caloric content. While choosing the patch to forage, granivores might avoid the ones with smaller, less preferred seeds. We tested a novel hypothesis that the production of different size seeds by a plant may be a strategy to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Seed‐granivore interactions are highly context‐dependent (Celebias & Bogdziewicz, 2023; Lichti et al., 2017; Ostoja et al., 2013). Several factors, such as the quality of the patch (Caccia et al., 2006), population size of granivores (Janova et al., 2016; Zwolak et al., 2021) and the availability of alternative food sources (Van Baalen et al., 2001), shape the decisions granivores make regarding encountered seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Seed‐granivore interactions are highly context‐dependent (Celebias & Bogdziewicz, 2023; Lichti et al., 2017; Ostoja et al., 2013). Several factors, such as the quality of the patch (Caccia et al., 2006), population size of granivores (Janova et al., 2016; Zwolak et al., 2021) and the availability of alternative food sources (Van Baalen et al., 2001), shape the decisions granivores make regarding encountered seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that among-population variation in germination response to environmental conditions resulted in different responses to climate change within species, which could mitigate the species' vulnerability to changing climate and provide opportunities for species adaptation and conservation (Chamorro et al 2017(Chamorro et al , 2018Cochrane et al 2015a). The sensitivity of germination to climate variability depends on the species' phenotypic plasticity, local adaption, and geographic distribution (Cochrane et al 2015b;Nicotra et al 2010).…”
Section: Introductionmentioning
confidence: 99%